PRINCIPLES OF PROFESSIONAL TRAINING OF BORDER GUARDS IN THE REPUBLIC OF INDIA - Бхіндер, Н. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The importance of our research is stipulated by the similarity of threats at the Ukrainian and Indian borders. The analysis of scientific literature and normative documents allows us to come to the conclusion that there is a need to study professional training of border guards in the Republic of India to implement creatively some of its elements, namely the principles of professional training of border guards in the Republic of India. The aim of the article is to define the notion «the principle of professional training of border guards», to analyze and classify the principles of professional training of border guards in the Republic of India and to describe the peculiarities of their implementation within the process of training border guard agencies speciaalists in details taking into consideration specific character of service activities in the particular border sectors. Thus, the principle of professional training of border guards means fundamental statements and regulations defining the requirements of methodical system aomponents of professional training of border guards. The author comes to the conclusion that considering the process of professional training of border guards in the Republic of India we can assert about exterior (national) and interior (agency-specific) principles, general principles (general pedagogical, psychological and pedagogical, organizational and pedagogical) and specific principles. General pedagogical principles concern scientific and innovation character, gradualness, connection of education and development, completeness, combination of various methods, equality. Psychological principles include consciousness, activity and independence, professional self-actualization and reflection. Organizational and pedagogical principles touch upon systemacy and succession, lifelong learning, contextuality, independent evaluation and flexibility. Also there is a number of specific principles; they are the following: formation of readiness to act in extreme conditions, special technical and human support, intensity, continuity of training, optimism and change of activities. It is necessary to admit that these principles are not universal and in order to achieve the pedagogical aim they should be used in combination. Further we are planning to investigate the structure and content of professional training of border guards in the Republic of India.